Impact of Hormone Replacement Therapy on stroke, and dementia due to Alzheimerâs disease on menopausal women (Medical Journal of Indonesia, 2002)
As a result of estrogen deficiency in menopausal women various health problems occur. Disorders of central nervous system such as stroke and dementia due to Alzheimerâs disease are frequently encountered in menopausal women. Estrogen plays an important role in the maintenance of the dense network of neural fibres connecting one nerve cell to another, and in the synaptic activity facilitating cognitive thought and memory. Hormone replacement therapy (HRT) reduced the risk of stroke by 30 % and a reduction of 60 % in risk of stroke mortality. The HRT influence cognitive functioning in menopausal women and may reduce the risk of developing dementia. Women who received HRT performed better on several tests of memory and logical reasoning than women taking placebo. Vaginal bleeding episodes constitute the major cause of womenâs dissatisfaction with combined HRT. (Med J Indones 2002; 11: 246-9). Keywords: HRT, menopause, memory, cognitive function, vaginal bleeding